Analisis Pengaruh Persepsi Kapabilitas Teknikal, Independensi Auditor Dan Quality Control Review Terhadap Kualitas Audit Sektor Publik - Dermawan Sugiarto (EBBANK, 2011)
This aims oh these research determine and analyze the technical capability, independence and quality control review to audit quality. The sample in this research is the auditor and Public Accountants according Announcement Apendix number 02/XII.2/05/2009 designated on Public Accountants Office.The method of analysis used in this study were multiple linear regression analysis. Conclusions obtained in this study are:1.    Perceptions of technical capability a positive impact on audit quality. This shows that the greater the technical capabilities possessed by auditor will give effect to increase the quality of audits.2.    Perception of independence does not give effect to audit quality. This shows that the high and low levels of auditor independence, it is likely to provide significant impact on audit quality possessed.3.    Perception quality control review does not give effect to the quality audit. It shows that the increase and decrease in quality control review does not provide a meaningful influence on the increase and decrease in audit quality.The implications of this research is to improve audit quality, interested parties should take into account the technical capabilities, independence and quality control review that is owned auditor, because based on the research results of these three factors are able to collectively influence the quality of audit. CPC and 44 KAP Audiot the audited financial statements of local governments should have a high ability to finish the problems related to the audit, an attitude that is not easily influenced by those who have an interest so that the resulting audit quality would be like to raise the quality auditor optimal.  The resulting audit, auditors should pay more attention to technical capability factor, because it is based on the results of technical research capabilities of the factors capable of making a positive impact on audit quality.